2018
DOI: 10.1177/0268355518772746
|View full text |Cite
|
Sign up to set email alerts
|

The femoral vein diameter and its correlation with sex, age and body mass index – An anatomical parameter with clinical relevance

Abstract: Background The femoral vein diameter is a critical factor when assessing endoprosthetic valve size for the treatment of chronic venous insufficiency. To examine the previously stated correlation between body mass index and femoral vein diameter and to re-assess the anatomical and physiological demands for a valve implant for chronic venous insufficiency treatment, we measured the femoral vein diameter in 82 subjects. Method Femoral vein diameters (164 legs) were measured with B-mode sonography both in supine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…The relationship between age and FVD is possibly a differential multi‐level correlation. Recent sonographical data suggest a significant difference in FVD between younger (< 30 years) and older subjects (Keiler et al, ). This trend toward a greater FVD seems to reverse in older subjects (> 60 years) both in vivo (Fronek et al, ) and in our present post mortem data.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…The relationship between age and FVD is possibly a differential multi‐level correlation. Recent sonographical data suggest a significant difference in FVD between younger (< 30 years) and older subjects (Keiler et al, ). This trend toward a greater FVD seems to reverse in older subjects (> 60 years) both in vivo (Fronek et al, ) and in our present post mortem data.…”
Section: Discussionsupporting
confidence: 71%
“…In general, BMI differences between different age cohorts could contribute to the age/FVD correlation since previous in vivo studies have demonstrated a positive correlation between FVD and BMI (Jeanneret et al, ; Fronek et al, ; Kröger et al, ; van Rij et al, ; Willenberg et al, ; Keiler et al, ) and epidemiological studies have demonstrated a distinct BMI increase between 25 years and 50 years age groups in the general population (Gostynski et al, ). On average, BMI more or less stagnates at older ages, though data for age > 65 years are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations